Գիտական հետազոտությունների և նորարարական լուծումների արդյունքների առևտրայնացման խնդիրները և զարգացման միտումները ՀՀ–ում - Աննա Բարոյան; Նարինե Մանուկյան (ՀՀ ԳԱԱ հրատ.)
Изучение, анализ коммерциализации научных исследований и инноваций и разработка прикладных решений имеют важное значение для нашей республики. При поддержке государства и частного сектора осуществляются программы, содействующие коммерцизации научных исследований и инноваций, однако этого недостаточно, поскольку налицо некоторые проблемы. The study of analysis of the scientific research and innovation commercialization, as well as the development of its theoretical and applied solutions are essential issue for our country. There are many ongoing and planned programs for the commercialization of scientific research and innovation by governmental and private sectors, although it is not enough, because there are still some persisting issues.
Keywords: Social Sciences; Economic Theory; Commerce